MANAGING LAND RESOURCES USING ARTIFICIAL SATELLITES - Tuyokulov Mironshoh, Amankeldiyev Tuychi Azim ugli, Begaliyev Og'abek Mavlonjon ugli (Journal of Applied Science and Social Science, 2026)
This article illuminates the theoretical and practical aspects of land resource management using satellite technologies. It analyzes the role of remote sensing technologies in the rational use of land resources, the monitoring of their condition, and their effective management. Furthermore, the potential applications of satellite imagery in the fields of agriculture, the cadastral system, and environmental monitoring are examined. The article also substantiates the importance of integration with modern technologies, including geographic information systems (GIS), global positioning systems (GPS), artificial intelligence, and big data. The research findings demonstrate the significance of satellite technologies for efficient land resource management and ensuring sustainable development.